Natural Products & Complementary Medicines: where are we up to? - Aljawharah AlQathama (University of Huddersfield Press, 2016)
The use of complementary and alternative medicine (CAM) has attracted much attention in recent years and has become a significant topic of debate within the healthcare sector. Many patients suffering from serious conditions such as cancer, Alzheimer's disease, diabetes and lower back pain seek alternative therapies including CAM biological products. Clinicians and healthcare practitioners need to be aware of the available clinical evidence relating to CAM-based therapies when advising patients and recommending options. This review presents the recent clinical data investigating the efficacy of CAM therapies for disease management among these groups of patients. A number of cancer drugs are listed which have been developed from natural sources and which have recently gained approval from the EMA and FDA based on clinical trials. Reasons for using CAM and the most frequently used CAM therapies are mentioned as well as the degree of improvement of quality of life based on patients' experiences.